PERSEPSI SISWA DALAM MENGIKUTI MATA PELAJARAN BAHASA INDONESIA TERHADAP NILAI HUMANISME DI SMAN 1 WONGSOREJO - Irdina Trya Hidayati Dayana; Muhammad Vikar Kuncoro; Muhammad Iqbal Ageng Prayogo; Denny Oktavina Radianto (KOLONI, 2023)
Education positions humans as social beings who interact with one another and makes it the most comfortable place for them (students) to grow and develop to the best of their ability to live in society. Education is basically a process of humanization. This research was conducted to determine the output of humanism values in Indonesian language learning at SMAN 1 Wongsorejo. Humanism education in learning Indonesian can be reflected in various aspects. Data collection in this study used limited questionnaires which were distributed to grade 2 students who received Indonesian language learning. The results of this study are that the value of humanism obtained by each student differs depending on the understanding and influence of oneself and the surrounding environment. The expected value of humanism as the output of learning Indonesian expected by researchers is based on students' perceptions that they have applied humanist values after participating in learning so that Indonesian influences students' views of the values that exist in humanism.  Keywords: Education, Indonesian Language Learning, Humanism